Data supporting exosome laden oxygen releasing antioxidant and antibacterial cryogel wound dressing OxOBand alleviate diabetic and infectious wound healing - Parvaiz A. Shiekh; Anamika Singh; Ashok Kumar (Data in Brief, 2020)
Hypoxia, reduced vascularization, elevated oxidative stress, and infection are critical clinical hallmarks of non-healing chronic diabetic wounds. The dataset presented here is in support of the development and evaluation of the exosome laden oxygen releasing OxOBand for treatment and management of diabetic and infectious wounds [1]. It describes the additional results in support of the development of OxOBand and its evaluation for diabetic wound healing. Exosomes were isolated from adipose-derived stem cells (ADSCs) and characterized through dynamic light scattering (DLS) and scanning electron microscopy (SEM). The encapsulation of exosomes by cells and its effect on migration of NIH3T3 cells under in-vitro condition is described. Further antioxidant polyurethane (PUAO) cryogel and oxygen releasing antioxidant (PUAO-CPO) cryogel scaffolds were fabricated as reported earlier [2,3] and NIH3T3, HaCaT and ADSCs were cultured on these scaffolds. “OxOBand”, the calcium peroxide containing oxygen releasing antioxidant polyurethane (PUAO-CPO) scaffold along with exosomes was evaluated in chronic wounds in diabetic rats. The wounds were also infected with Staphylococcus aureus (S. aureus), and Pseudomonas aeruginosa (P. aeruginosa) bacteria and OxOBand was further evaluated for the healing of these infectious diabetic wounds. Interpretation of this data can be found in a research article title “Exosome laden oxygen releasing antioxidant and antibacterial cryogel wound dressing OxOBand alleviate diabetic and infectious wound healing, Shiekh et. al., Biomaterials, 2020 [1].